Analysis the “Memirsa” Skill Learning Model for Primary School Students - Wahyuningsih, Yuli; Purnanto, Arif Wiyat (research, training and philanthropy institution Natural Aceh, 2024)
The purpose of this research is to find out the memirsa learning model in class IV A SDIT Muhammadiyah Bandongan, the research method used is qualitative research with the type of in-depth observation (Natural Observation). Data collection methods were observation, interviews, and field notes conducted for one month at the research location. The results showed that the visual learning model had been implemented with a percentage of 40%, including aspects of visual literacy as much as 60% and critical literacy as much as 40%. In the visual Mliteracy stage, flushing learning is included in the early phase, characterized by learners' understanding or response to simple multimodal texts that are familiar and predictable in structure. While in the type of critical mamirsa, learning to view is in the exploration phase which is characterized by integrating strategies in understanding, recognizing, and interpreting the content, purpose and form of multimodal texts. In learning to view is supported by the use of media in the form of textbooks with a percentage of 61%, power point 31% and wall crafts 8%.